Balinese Art-Oriented Digital Comic Media for Pancasila Education Subjects to Improve Learning Outcomes - Laksana, Made Arya Dharma; Tegeh, I Made; Widiastini, Ni Wayan Eka (Universitas Pendidikan Ganesha, 2025)
Civics education often faces challenges in delivering the topic of diversity in an engaging and easily comprehensible manner for students. The lack of innovative instructional media that incorporate local cultural values has become an obstacle in improving students' learning outcomes. This study aims to develop and evaluate the effectiveness of a digital comic media oriented to Balinese art in enhancing the learning outcomes of fourth- grade students on the topic of ethnic, social, and cultural diversity in Indonesia. This is a development research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects included one teacher and fourth-grade students as trial participants. Data were collected through observation, interviews, and tests, using instruments such as validation sheets, response questionnaires, and learning outcome tests. Data were analyzed using descriptive quantitative techniques and paired t-tests. The results showed that the Balinese art-oriented digital comic media had very high content validity (index 0.93–1.00), high practicality based on teacher (97.5%) and student (98.33%) responses, and significant effectiveness in improving students’ learning outcomes (p = 0.017 < 0.05). The conclusion of this study is that the Balinese art-oriented digital comic is valid, practical, and effective as an innovative instructional media to improve students' learning outcomes. The implication of this study suggests that integrating local culture into digital learning media can enhance students’ interest, motivation, and meaningful understanding.